Adaptasi Fisiologis Tubuh Terhadap Latihan Aerobik Dan Anaerobik Dalam Meningkatkan Ketahanan Otot: Penelitian - Muhammad Andri Fahrian; Sabar Imanuel Hutabarat; Jumadi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Aerobic and anaerobic exercises represent two primary forms of physical activity that induce distinct physiological changes in the human body, particularly in bolstering muscle endurance. This study examines the mechanisms of physiological adaptations from aerobic training (such as long-distance running or cycling), which relies on the oxidative energy system, and anaerobic training (like sprinting or repeated weightlifting), which depends on the glycolytic and phosphocreatine systems. Aerobic adaptations include an increase in mitochondrial density, enhanced oxidative enzyme activity (e.g., citrate synthase), and expanded muscle capillarization, promoting more efficient oxygen utilization and delaying fatigue onset. Conversely, anaerobic adaptations involve hypertrophy of type II muscle fibers, improved lactate buffering capacity (e.g., lactate dehydrogenase enzyme), and better ATP-CP recovery processes, enabling sustained muscle contractions at high intensities. Experiments on trained subjects (aged 20-35 years) over 12 weeks revealed notable improvements in muscle endurance for both aerobic and anaerobic groups, with a combined approach yielding superior overall benefits. These findings underscore that selecting exercises based on goals (aerobic for long-term endurance, anaerobic for highintensity tolerance) is most effective for athletes and the general population. Hybrid training programs are recommended to maximize adaptive outcomes.